Alleviation of Salt Stress in Upland Rice (Oryza sativa L. ssp. indica cv. Leum Pua) Using Arbuscular Mycorrhizal Fungi Inoculation - Tisarum, Rujira; Theerawitaya, Cattarin; Samphumphuang, Thapanee; Polispitak, Kanyamin; Thongpoem, Panarat; Singh, Harminder Pal; Cha-um, Suriyan (Frontiers in Plant Science, 2020)
Arbuscular mycorrhizal fungi (AMF) symbionts not only promote the growth of host plant but also alleviate abiotic stresses. This study aimed to investigate the putative role of AMF in salt stress regulation of upland pigmented rice cv. Leum Pua (LP) comparing with Pokkali salt tolerant (positive check). In general, LP is a variety of glutinous rice that contains anthocyanin pigment in the black pericarp, due to which it possesses high antioxidant activities compared to non-pigmented rice. Pot experiment was conducted to evaluate the impact of inoculated AMF, Glomus etunicatum (GE), Glomus geosporum (GG), and Glomus mosseae (GM) strains, in the LP plantlets subjected to 0 (control) or 150 mM NaCl (salt stress) for 2 weeks in comparison with Pokkali (a salt tolerant rice cultivar), which was maintained as a positive check. Root colonization percentage under NaCl conditions ranged from 23 to 30%. Na+ content in the flag leaf tissues was increased to 18–35 mg g–1 DW after exposure to 150 mM NaCl for 14 days in both inoculated and un-inoculated LP plants, whereas Na:K ratio was very low in cv. Pokkali. Interestingly, sucrose content in the flag leaf tissues of un-inoculated LP plants under salt stress was increased significantly by 50 folds over the control as an indicator of salt stress response, whereas it was unchanged in all AMF treatments. Fructose and free proline in GE inoculated plants under salt stress were accumulated over control by 5.75 and 13.59 folds, respectively, for osmotic adjustment of the cell, thereby maintaining the structure and functions of chlorophyll pigments, Fv/Fm, ΦPSII, and stomatal function. Shoot height, flag leaf length, number of panicles, panicle length, panicle weight, and 100-grain weight in GE inoculated plants of cv. LP under salt stress were maintained similar to cv. Pokkali. Interestingly, cyanidin-3-glucoside (C3G) and peonidin-3-glucoside (P3G) in the pericarp of cv. LP were regulated by GE inoculation under salt stress conditions. In summary, AMF-inoculation in rice crop is a successful alternative approach to reduce salt toxicity, maintain the yield attributes, and regulate anthocyanins enrichment in the pericarp of grains.